2013
DOI: 10.1038/jes.2013.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of temporally refined land-use regression models predicting daily household-level air pollution in a panel study of lung function among asthmatic children

Abstract: 1Regulatory monitoring data and land-use regression (LUR) models have been widely used for estimating individual exposure to ambient air pollution in epidemiologic studies. However, LUR models lack fine-scale temporal resolution for predicting acute exposure and regulatory monitoring provides daily concentrations, but fails to capture spatial variability within urban areas. This study coupled LUR models with continuous regulatory monitoring to predict daily ambient nitrogen dioxide (NO 2 ) and particulate matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…While seasonal models are of interest to understand how particular forms of the built environment interact with meteorological and climatological factors to change the spatial distribution of air pollutants throughout the year, the ultimate contribution of air pollution models is to improve exposure assessment for epidemiological studies. To this end, Johnson et al (2013) demonstrated that temporal refinement of a NO 2 LUR model with regulatory monitoring data can improve exposure estimation for research on short-term effects on health.…”
Section: Discussionmentioning
confidence: 99%
“…While seasonal models are of interest to understand how particular forms of the built environment interact with meteorological and climatological factors to change the spatial distribution of air pollutants throughout the year, the ultimate contribution of air pollution models is to improve exposure assessment for epidemiological studies. To this end, Johnson et al (2013) demonstrated that temporal refinement of a NO 2 LUR model with regulatory monitoring data can improve exposure estimation for research on short-term effects on health.…”
Section: Discussionmentioning
confidence: 99%
“…1 In terms of same day exposures (lag 0), this meta-analysis found small positive associations between the risk of hospitalisation or mortality for stroke and each of PM 2.5 , PM 10 and NO 2 and in terms of stroke subtypes, positive associations between ischaemic stroke and 'overall' exposure (typically the shortest lag available) to PM 2.5 and NO 2 and between haemorrhagic stroke and 'overall' exposure to NO 2 . 1 However, our study was relatively small, with our analysis based on 1758 strokes of which 1311 were ischaemic and 256 haemorrhagic.…”
Section: Discussion Main Findingsmentioning
confidence: 71%
“…Although few studies are able to consider these disease categories separately, a small study in Mantua, Italy, 27 found evidence of a positive association between PM 10 exposure and same day hospital admission for TACI in men only and for LACI in men and women. When we investigated these subtypes in our analysis (table 5), we found small non-significant, though positive, associations between TACI (number of cases=187) and both PM 2.5 and PM 10 , with the percentage increase in risk per 10 mg/m 3 increase in pollutant estimated at 5.9% (95% CI −15.9% to 33.3%) for PM 2.5 and 2.5% (95% CI −12.4% to 19.9%) for PM 10 . However, the CIs were again particularly wide.…”
Section: Stroke Subtypesmentioning
confidence: 75%
See 2 more Smart Citations